Why Home Delivery After Full Antenatal Care Follow-Up in Southern Ethiopia? An Exploratory-Descriptive Qualitative Study - Toja E; Abebe A; Mekonen N; Baza D (Dove Medical Press, 2022)
Eshetu Toja,1 Amene Abebe,1 Niguse Mekonen,1 Daniel Baza2 1Department of Public Health, Wolaita Sodo University, Wolaita Sodo, Ethiopia; 2Department of Nursing, Wolaita Sodo University, Wolaita Sodo, EthiopiaCorrespondence: Amene Abebe, Email ameneabe@gmail.comBackground: Pregnant women who had full antenatal care follow-up are expected to give birth in health facilities. However, in Ethiopia, after full antenatal care booking, many women still prefer to give birth at home. Thus, the purpose of this study was to explore and describe why women give childbirth at home after full antenatal care follow-up in the study setting.Methods: Exploratory-descriptive qualitative design was conducted in Humbo and Abala Abaya districts, Southern Ethiopia, from June to September 2020. Nine in-depth interviews and four focus group discussions were held with purposively selected participants. Women who gave birth at home after attending equal to or more than four antenatal care appointments in the last year were included. The collected data were majorly analyzed by inductive thematic analysis technique, but deductive analysis was also applied whenever the potential themes needed further enrichment. A thick description of the findings is done in the respective heading and sub-heading using participants' verbatim quotations.Results: A total of 9 in-depth interviews and four focus group discussions comprising 35 participants was conducted. Three major themes and nine sub-themes emerged from the data. Socio-cultural and community influences, socio-economic obstacles, and health system-related barriers are the major themes identified. Traditional practices, personal beliefs, social norms, knowledge, and attitude about institutional delivery, household economic capability, decision-making capacity of the women, delivery service quality, and service providers related barriers are the sub-themes defining the home delivery experience of women after full antenatal care follow-up in the study setting.Conclusion: In this study, socio-economic, cultural, and health system-related barriers are major reasons for home delivery. Improvement of public awareness on the risk of home delivery and elimination of its facilitative social norms, empowerment of women's economic, educational, and decision-making capability and healthcare workers' and health facilities' capacity are recommended.Keywords: antenatal care, follow-up, full antenatal care, home delivery, institutional delivery